Leptin as a Physiological Mediator of Energetic Trade-Offs in Ecoimmunology: Implications for Disease - French, Susannah S. (Integr Comp Biol, 2011)
Organisms must distribute sufficient energy among different and often competing physiological systems. This task can become challenging, however, as resources are often limiting, resulting in energetic trade-offs. For example, energetically based trade-offs between the reproductive and immune systems are common across taxa, yet the regulatory mechanisms underlying these trade-offs remain unclear. The adipose tissue hormone leptin is an ideal candidate for the modulation of energetic trade-offs between different physiological systems as this hormone serves as a gage of fat reserves and also modulates a range of physiological activities including the reproductive and immune processes. This article presents a review of the evidence for the role of leptin as a modulator of energetic trade-offs with the immune system and suggests its importance in disease ecology. In addition, we provide a case study of the ornate tree lizard (Urosaurus ornatus), testing whether leptin is involved in mediating a well-documented influence of energy state on the trade-off between reproductive activity and immune function. Overall, the combined results suggest that leptin serves as a proximate endocrine signal of available energy to the immune system, and therefore likely to affect susceptibility to diseases.